Decision support system for stall and workshop identification (DSSSWI) / Fazilah Othman - Fazilah, Othman (2013)
Decision Support System for Stall/Workshop Identification (DSSSWI) system is designed to help tenants find the exact location of available rental stall/workshop. It is also developed to overcome a few tenant's problems such as time, energy and money consuming. Besides, this research is to develop DSSSWI system integrates with Decision Support System (DSS) and Geographic Information System (GIS). The use of DSS is to help new tenants find and choose the best stall/workshop based on their interest and need and the use of GIS is to view the exact location of the stall/workshop through Google map. This system consists of two target user which is the tenants and UPD officer from Perlis. The input of this system will be Parliament, Dewan Undangan Negeri (DUN), and rental price. Then, this system will analyze by using these input to view the exact location of available rental stall / workshop. This research methodology consists of five stages which are gathering information, data collection, system design, implementation and evaluation. The data were gathered from District Administration Unit (UPD), Office State Sectary of Perlis. This system is a web-based system. Besides, this system is developed by using Hypertext Preprocessor (PHP) as a programming language, MySQL as a database and Apache as a web server. Lastly, this system is successfully developed and all the function and features are running and functioning well.